Martin Luther. Volume I a Christian between reforms and modernity (1517-2017) - Melloni, Alberto (Berlin ; Boston : De Gruyter, 2017)
The three volumes present the current state of international research on Martin Luther's life and work and the Reformation's manifold influences on history, churches, politics, culture, philosophy, arts and society up to the 21st century. The work is initiated by the Fondazione per le scienze religiose Giovanni XXIII (Bologna) in cooperation with the European network Refo500. This handbook is also available in German.
The Universalgeschichtlich Role of the Reformation according to Idealism and Historicism within German CultureLuther and the Revolution of the Individual; Luther and Marxism; Reformation Protestantism and theSpirit of Capitalism; Luther in Catholic Historiography and Theology: The Nineteenth and Twentieth Centuries; Luther and the Third Reich: Consent and Confession; Luther in Protestant Historiography and Theology in the Nineteenth and Twentieth Centuries; Communicating Luther; The Past in the Present: Remembering Luther in 1617, 1817, and 1883; Architecture and Reformation
Martin Luther in Portraits
Description based on online resource; title from digital title page (viewed on Mar. 23, 2018).
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Luther, Martin, -- 1483-1546.; Luther, Martin, -- 1483-1546.; Reformation; Reformation; RELIGION / Christianity / Protestant; Electronic books